Using Canva to Improve the Students’ Writing of Greeting Card (A Case Study at One of Senior High School in Tasikmalaya) - Aulanisa, Ersa; Thoyyibah, Luthfiyatun; Rohayati, Dedeh (Journal of English Education Program (JEEP), 2025)
Teacher and students can utilize technology-based learning media, such as the Canva. The aim of this study was to explore the use of Canva as a digital tool in English language learning. The study was conducted at a senior high school in Tasikmalaya. Qualitative case study was applied as data collection methods were research question observations and interviews. The researcher conducted observation and interviews to five students from class X-9. Semi-structured interview data were collected through one-on-one interviews and audio recordings for further analysis. The findings indicate that Canva has a positive or effective influence to improve students’ mastery of writing skills. Moreover, the findings suggest that students perceive Canva to be a potentially beneficial tool for improving their writing skills, digital literacy, and creativity. However, the results of the study revealed that students’ perceptions about Canva were various. Despite the challenges encountered by students, most of students perceived it as being a potential benefit to improve their writing abilities. The teacher further support the use of Canva for creating student greeting cards, demonstrating its effectiveness in enhancing their design skills and personal expression. In conclusion, the findings suggest Canva is a popular and influential medium for students, giving them a chance to express themselves, enhance their language abilities, and discover new talents. In addition, incorporating structured educational interventions or guided Canva assignments may prove beneficial in supporting students’ language learning journey through Canva. Understanding the influence of cultural and societal factors on students’ Canva preferences can foster cross-cultural communication and enhance their English language development.